Analysis and improvements of manpower productivity in a port operation - Yong, Paul Jie (2014)
The purpose of this report is to analysis the current manpower productivity in a port operation via the study of the current manpower allocation process. The developed simulation model, build using Java Development Kit 1.7, effectively mirrored the actual manpower allocation process happening in a XYZ’s port. Propose solution such as increasing the existing numbers of manpower group and improving the overall skill level of the workforce, are being implemented and tested out in the simulation model, and the results are being tabulated and analysed. Other key factors which is affecting the current manpower productivity are also being discussed in the later chapter. The author believed that although there is no doubt that better equipment and technology will bring about better manpower productivity in the port, it is also important to relook and improve on the fundamental operations process. Hence the focus of this report is on how the current manpower allocation process affects the current manpower productivity and how this can be optimise.